Coberturas do solo e uso de manta agrotêxtil (TNT) no cultivo do meloeiro - Braga, Marcos B.; Marouelli, Waldir A.; Resende, Geraldo M.; Moura, Magna S. B.; Costa, Nivaldo D.; Calgaro, Marcelo; Correia, Joselina S. [UNESP] (FapUNIFESP (SciELO), 2017)
The use of ground cover in melon production could be an alternative in the region of the São Francisco Valley, where the challenge is to produce in quantity and quality in the off season. This study aimed to evaluate the influence of five soil cover types, with and without nonwoven blanket (TNT) cover on productivity and quality of melon fruits in non-traditional growing season in the São Francisco River region, Petrolina, Pernambuco State, Brazil. The experiment was carried out in 2009 and 2010, during June to August. Experimental design was randomized blocks with three replications in a factorial arrangement 6x2. Treatments included five types of soil cover (black polyethylene and black-silvery double face polyethylene film, coconut shell, buffelgrass straw and sugarcane bagasse), uncovered soil treatment, and the plant covers previously mentioned with or without TNT. The number of fruits per plant ranged from 1.11 to 1.70 fruits without significant differences between treatments, except for the treatment with coconut shell which showed a worse performance in 2010. The highest and lowest production of fruits per plant were obtained using black-silvery double face polyethylene film and uncovered soil (2.91 and 1.91 kg/plant, respectively). The soil covers black-silvery double face polyethylene film, buffelgrass straw and sugarcane bagasse showed higher marketable yield or similar to the other treatments ranging between 35.60 and 58.20 t/ ha. In general, the physical characteristics and fruit quality were little influenced by soil cover and TNT. In terms of water productivity index (iPA), considering the two crop cycles, black-silvery double face polyethylene film, sugarcane bagasse, buffelgrass straw, black polyethylene and coconut shell showed a better iPA, varying between 113.8 and 133.9 L/kg of fresh fruit, while uncovered soil showed a worse value (164.1 L/kg).
Soil covers on the melon cultivation under nonwoven blanket
Keywords: Cucumis melo; Fruit quality; Mulching; Plant cover; Yield